Analysis of indications and route of hysterectomy for benign conditions - Patne, Smita S.; Upadhye, Aditi J.; Upadhye, Jayshree J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysterectomy is the most common operation performed by gynecologist, next to caesarean section. The primary focus of this study was to review the indications and surgical technique of hysterectomy. Methods: This retrospective study was performed in the department of Obstetrics and gynecology, in collaboration with Department of Pathology. All women in the reproductive age group and post-menopausal age who underwent hysterectomy with or without salpingo-oophorectomy were included in this study. Results: In our study, out of 100 patients, clinical indication was fibroid in 45 (45%) patients, menorrhagia in 15 (15%) patients, adenomyosis in 25 (25%) patients, uterovaginal prolapse in 5 (5%) patients, endometrial polyp in 5 (5%) patients and ovarian tumor in 5 (5%) patients. Histo-pathological diagnosis was leiomyoma in 55 (55%), adenomyosis in 30 (30%), endometrial polyp in 5 (5%), endometrial hyperplasia in 5 (5%) and serous cystadenoma of ovary in 5 (5%). Abdominal hysterectomy was performed in 46 (46%) patients, vaginal hysterectomy in 44 (44.33%) patients while laparoscopic hysterectomy was performed in 5 (6.66%) patients. Conclusions: In this study, most common indication for hysterectomy was fibroid uterus and it was correlated well with histopathology. Abdominal & vaginal hysterectomies were performed in almost equal number.